(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2024)
The role of traditional underutilized food in fulfilling the nutritional requirement of rural communities is acknowledged across the world. The Sikkim and Darjeeling Himalaya is considered as one of the hotspot of diverse underutilized nutritious crops and vegetables. Though the earlier generation used those diverse traditional nutri-crops to fulfill food and nutritional requirement but their usage and cultivation has declined over the period. The new generation is not aware of the nutritional values of these local crops. In this context, the present study was conducted to document the traditional nutri-crops of Sikkim and Darjeeling Himalaya, and to suggest future policies for mainstreaming of these traditional crops into the farmers’ existing cropping system. A new participatory nutrition profiling technique was developed and validated for assessing the nutritional status of documented crops in the study from a sample of 560 farmers. The findings revealed that the nutritive value of Phapar (Fagopyrum dibotrys-4.47) was highest followed by Chuche Karela (Momordica charantia L.- 4.38) and Simrayo (Nasturtium officinale R.Br.- 4.34). The crops with highest malnutrition potential were Sil timbur (Litsea cubea (lour.) pers. - 4.37) followed by Kinema (Glycine max-4.33) and Simal tarul (Manihot esculenta Crantz -4.32), Batulpate (Cissampelos pareira L.- 4.30). The major recommendation for popularizing the traditional nutria-crops were ‘Ensuring better price for traditional nutria-crops (81%)’ followed by ‘Start research initiative specifically on local unexplored nutria-crops to enhance their production and productivity (80%)’, and ‘Demonstrating the potential of indigenous nutri-crops in fighting malnutrition through extension agents (78%)’